1985
DOI: 10.1037/0022-0167.32.3.431
|View full text |Cite
|
Sign up to set email alerts
|

Relation of racial identity attitudes to self-actualization and affective states of Black students.

Abstract: 1 Although Cross (1978) conceptualized the internalization-commitment stage as a separate stage, he concedes that it is difficult to figure out where it fits in the general model, because ostensibly similar behavioral styles may accompany the immersion-emersion stage as well. In our own work, we have chosen not to operationalize the fifth stage because it seems to confound general styles (e.g., assertiveness or gregariousness) with racial identity in a way that we have been unable to separate. 431This document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
249
4
3

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(281 citation statements)
references
References 23 publications
(37 reference statements)
7
249
4
3
Order By: Relevance
“…Literature that attests to the relationship between social identity-whether labeled racial identity (Parham & Helms, 1981, 1985a, 1985b, ethnic identity (Elizur, 1984;Phinney, 1990), ethnic self-identity (Driedger, 1976), or collective self-esteem (Luhtanen & Crocker, 1992)-and behavioral and psychological adjustment abounds. Moreover, recent research (Sherwin, 1994(Sherwin, , 1997 suggests a strong positive relationship exists between collective self-esteem and hope.…”
Section: Hope and Culturementioning
confidence: 99%
“…Literature that attests to the relationship between social identity-whether labeled racial identity (Parham & Helms, 1981, 1985a, 1985b, ethnic identity (Elizur, 1984;Phinney, 1990), ethnic self-identity (Driedger, 1976), or collective self-esteem (Luhtanen & Crocker, 1992)-and behavioral and psychological adjustment abounds. Moreover, recent research (Sherwin, 1994(Sherwin, , 1997 suggests a strong positive relationship exists between collective self-esteem and hope.…”
Section: Hope and Culturementioning
confidence: 99%
“…Evidências empíricas, como as de Parham & Helms (1985), sugerem que as pessoas submetidas à discriminação tendem a apresentar autoconceito pobre, baixa auto-estima, auto-realização pobre, ansiedade e depressão. O indivíduo, tem a sensação de não se 'encaixar' realmente em nenhum grupo, pois internaliza os valores 'brancos' e é desqualificado por ser negro, de tal forma que passa a desvalorizar-se como pessoa.…”
Section: O Preconceito Silenciadounclassified
“…This racial identity scale outlines the mental health stability, disorders, or wellbeing associated with the Cross/Helms Black racial identity scales. Studies using the RIAS found African Americans in the preencounter stage of racial identity had a poorer psychological wellbeing, lower self-actualization, and lower self-esteem [3,9,10]. Individuals in the pre-encounter stage, also have more symptoms and higher levels of psychopathology, depression, anxiety, paranoia, hypersensitivity, feelings of personal inadequacy, and psychological distress in comparison to individuals in the encounter, immersion/emersion, and internalization stages.…”
Section: Black Racial Identity and Mental Healthmentioning
confidence: 99%